The Existence Of The Police Of The Republic Of Indonesia In Managing Anarchic Actions On Haruku Island - Titahelu, Juanrico Alfaromona Sumarezs (Fakultas Hukum, Universitas Sawerigading Makassar, 2022)
Indonesia is a country that adheres to a democratic system, so the position of the people occupies the highest position.In various places in the world there are conflicts and even violence between groups. One of them, namely Maluku, is currently dealing with several cases of conflict between groups or countries, including residents of Kariu and residents of the Ori hamlet, which started from a verbal argument between two residents of Kariu and residents of the hamlet. Geographically, the country of Kariu borders Pelau and Ori, in terms of the anatomy of the problem, this crime involves people in the sense of the person of the perpetrator and the victim. Anarchy is a physical disorder in civil society in the form of clashes, mass fights, killings, looting, and destruction of public facilities and infrastructure, as well as private or other non-criminal facilities. According to the